Stereoselective synthesis of (2R, 3S, 22R, 23E)-6, 6-ethylenedioxy-22-hydroxy-2, 3-isopropylidenedioxy-24-methyl-5 alpha-cholest-23-ene: An intermediate for the synthesis of castasterone, dolichosterone and brassinolide - Hazra, Braja G.; Kumar, T. P.; Pore, V. S. (Indian Journal of Chemistry Section B-Organic Chemistry including Medicinal Chemistry, 2005)

Stereoselective syntheses of unnatural steroidal C(20R) aldehydes by ionic hydrogenation of C-20 tertiary alcohols - Shingate, Bapurao B.; Hazra, Braja G.; Pore, Vandana S.; Gonnade, Rajesh G.; Bhadbhade, Mohan M. (Tetrahedron Letters, 2006)
Syntheses of three unnatural steroidal C(20R) aldehydes have been realised from 16-dehydropregnenol one acetate. The salient feature of the synthesis is the ionic hydrogenation of C-20 tertiary alcohols leading to the formation of the C(20R) unnatural isomer with complete stereoselectivity. Oxidative hydrolysis of the dithiane moiety furnished the C(20R) aldehydes. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: 1; 3-dithiane; ionic hydrogenation; oxidative hydrolysis; stereoselective synthesis; unnatural C-20 aldehydes

Syntheses of 1,2-amino alcohols and their applications for oxazaborolidine catalyzed enantioselective reduction of aromatic ketones - Vatmurge, Namdev S.; Hazra, Braja G.; Pore, Vandana S. (Australian Journal of Chemistry, 2007)
Six new chiral 1,2-amino alcohol derivatives have been synthesized starting from (1R, 2R)-2-amino-1-phenylpropane-1,3- diol. Asymmetric reduction of aryl ketones with in-situ generated oxazaborolidine from these amino alcohol derivatives and BH3 center dot Me2S afforded secondary alcohols with good yield and moderate to high enantiomeric excess.

Synthesis and antimicrobial activity of beta-lactam-bile acid conjugates linked via triazole - Vatmurge, Namdev S.; Hazra, Braja G.; Pore, Vandana S.; Shirazi, Fazal; Chavan, Pradnya S.; Deshpande, Mukund V. (Bioorganic & Medicinal Chemistry Letters, 2008)
Synthesis of novel 1,2,3-triazole-linked beta-lactam-bile acid conjugates 17-24 using 1,3-dipolar cycloaddition reaction of azido beta-lactam and terminal alkyne of bile acids in the presence of Cu( I) catalyst ( click chemistry) have been realized. These molecules were evaluated in vitro for their antifungal and antibacterial activities. Most of the compounds exhibited significant antifungal and moderate antibacterial activity against all the tested strains. (c) 2008 Elsevier Ltd. All rights reserved.

Synthesis and biological evaluation of bile acid dimers linked with 1,2,3-triazole and bis-beta-lactam - Vatmurge, Namdev S.; Hazra, Braja G.; Pore, Vandana S.; Shirazi, Fazal; Deshpande, Mukund V.; Kadreppa, Sreenath; Chattopadhyay, Samit; Gonnade, Rajesh G. (Organic & Biomolecular Chemistry, 2008)
We report herein the synthesis and biological evaluation of bile acid dimers 11-18 linked through 1,2,3-triazole and bis-beta-lactam. The dimers 11-18 were synthesized using 1,3-dipolar cycloaddition reaction of diazido bis-beta-lactams 3, 4 and terminal alkynes 7-10 derived from cholic acid/deoxycholic acid in the presence of Cu(I) catalyst (click chemistry). These novel molecules were evaluated in vitro for their antifungal and antibacterial activity. Most of the compounds exhibited significant antifungal as well as antibacterial activity against all the tested fungal and bacterial strains. Moreover, their in vitro cytotoxicities towards HEK-293 and MCF-7 cells were also established.

Synthesis of chimeric tetrapeptide-linked cholic acid derivatives: impending synergistic agents - Bavikar, Sudhir N.; Salunke, Deepak B.; Hazra, Braja G.; Pore, Vandana S.; Dodd, Robert H.; Thierry, Josiane; Shirazi, Fazal; Deshpande, Mukund V.; Kadreppa, Sreenath; Chattopadhyay, Samit (Bioorganic & Medicinal Chemistry Letters, 2008)
Tetrapeptides derived from glycine and beta-alanine were hooked at the C-3 beta position of the modified cholic acid to realize novel linear tetrapeptide-linked cholic acid derivatives. All the synthesized compounds were tested against a wide variety of microorganisms (Gram-negative bacteria, Gram-positive bacteria and fungi) and their cytotoxicity was evaluated against human embryonic kidney (HEK293) and human mammary adenocarcinoma (MCF-7) cell lines. While relatively inactive by themselves, these compounds interact synergistically with antibiotics such as fluconazole and erythromycin to inhibit growth of fungi and bacteria, respectively, at 1-24 mu g/mL. The synergistic effect shown by our novel compounds is due to their inherent amphiphilicity. The fractional inhibitory concentrations reported are comparable to those reported for Polymyxin B derivatives. (c) 2008 Elsevier Ltd. All rights reserved.
Keywords: Antimicrobial activity; Cholic acid; Cytotoxicity; Synergism; Tetrapeptide

Synthesis and antimicrobial activity of novel oxysterols from lanosterol - Shingate, Bapurao B.; Hazra, Braja G.; Salunke, Deepak B.; Pore, Vandana S.; Shirazi, Fazal; Deshpande, Mukund V. (Tetrahedron, 2013)
Chemically diverse oxysterols and their synthetic manipulations were carried out from variety of Delta(8(9)_) lanosterol derivatives and evaluated for their in vitro antimicrobial activities. Most of the synthesized oxysterols exhibited significant antifungal activity against the tested strains. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Allylic oxidation; antibacterial activity; Antifungal activity; Dihydroxylation; Oxygenated steroids